Entropic stochastic resonance and super-harmonic stochastic resonance in a dichotomous fluctuating potential. (1st August 2022) - Yang, Jingwei; Chang, Boyuan; Zhang, Lu
Abstract: When a Brownian particle moves in a confined space, the boundaries of the confined space can form an entropic barrier and thus induce the classical entropic stochastic resonance (ESR) phenomenon. This paper introduces a dichotomous fluctuating potential into the classical ESR model and studies the dynamics and ESR phenomena of the confined particle. It is shown that the amplitude of each harmonic component of both the horizontal and vertical displacements of the confined particle appears in various types of ESR phenomena, such as single-peak ESR, double-peak ESR, or even multi-peak ESR. This multi-peak ESR phenomenon is caused when the different dynamical states of the confined particle (under the joint action of the energy and entropy potentials) reach the optimal equilibrium. The results of this paper will help to understand the mechanism of stochastic dynamics of particles in confined spaces.